Child Character Education Through Health and Sports Physical Education - Leni Apriani; Mimi Yulianti; Joni Alpen; Aprillia Maharani Putri (UNIB Press, 2023)
The purpose of this study was to determine the results of the formation of children's character through play activities in physical education, sports and health. The type used in this research is descriptive quantitative. Data collection was used by distributing research questionnaires. The population and sample in this study were Class VIII SMP Negeri 2 Rambah Samo, Rokan Hulu Regency, which consisted of 60 students. The instrument to be used in this research is a questionnaire. Based on the research data obtained in this study it can be concluded that Character Education Through Physical Education Sports Health is in the